2020
DOI: 10.1111/mcn.13028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maternal and neonatal blood Vitamin D level: Study from Pakistan

Abstract: In Pakistan, there is limited evidence for the levels and relationship of 25 (OH) Vitamin D (25(OH)D) status in pregnant women and their newborns, while the association between maternal 25(OH)D and newborn anthropometric measurements remains unexplored. Sociodemographic data were collected from 213 pregnant mothers during their visit to a tertiary care hospital at the time of childbirth. Anthropometric measurements were performed on all mothers and their newborns and blood samples collected from both for 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
3
21
0
3
Order By: Relevance
“…In the study done by Rabbani et al they evaluated the Correlation between maternal and neonatal blood VD level among 213 pregnant women and their neonates and their results showed strong positive association between maternal and newborn 25(OH)D levels (p < 0.001) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the study done by Rabbani et al they evaluated the Correlation between maternal and neonatal blood VD level among 213 pregnant women and their neonates and their results showed strong positive association between maternal and newborn 25(OH)D levels (p < 0.001) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is more prevalent in children, pregnant and nursing women in Pakistan [ 9 ], India [ 10 ], and Germany [ 11 ]. A study reported from Karachi, vitamin D deficiency in 75% of children associated with low socioeconomic communities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infants with nutritional rickets often present at early stage when exclusive or partial breastfeeding is predominant (12). Studies showed that the concentration of serum 25(OH)D in mothers was positively correlated with that in cord blood of newborns (13,14), but the correlation between mothers and infants was unclear. It was reported that vitamin D levels in the human breast milk were positively related to maternal serum concentrations of vitamin D (15).…”
Section: Introductionmentioning
confidence: 99%